(untitled) (Bangladesh Journal of Agricultural Research, 2013)
In vitro propagation of strawberry was conducted at the Biotechnology Lab. of BARI, Joydebpur, Gazipur. For shoot induction, five BAP concentrations viz., 0.0 (Control), 0.5, 1.0, 1.5, and 2.0 mg/l and for root induction four IBA concentrations viz., 0.0 (Control), 0.5, 1.0, and 1.5 mg/l were used. The highest average number of shoots (7) and the highest average length (3.34 cm) of shoot was observed at the concentration of 0.5 mg/l BAP. The highest average number of leaves (5) was also observed at the same concentration. Among the five rooting concentrations, IBA @ 0.5 mg/l showed the best performance in all the parameters studied. The highest number (6) of roots/culture and the longest (3.05 cm) roots were also obtained from this concentration. Half strength MS media without IBA concentration did not show any response regarding root induction. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16973 Bangladesh J. Agril. Res. 38(3): 467-472, September 2013